Hubungan Antara Self-Compassion Terhadap Loneliness Pada Mahasiswa Rantau Semester Awal di Universitas Negeri Surabaya - Khonsa Muna Wandana; Desi Nurwidawati (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2024)
The purpose of this study was to determine the relationship between self-compassion and loneliness in early semester overseas students at Surabaya State University. The research method used is quantitative. The research instrument used an adaptation of the Self-Compassion Scale (SCS) and the UCLA Loneliness Scale Ver 3. The research sample amounted to 177 students and sampling in this study using purposive sampling with the criteria of undergraduate students of Psychology, Surabaya State University class of 2023 and domiciled outside Surabaya. The data collection technique used a questionnaire with a Likert scale. Data processing using Pearson Product Moment correlation analysis, the results of the correlation coefficient value (r = 0.427) with a p-value of 0.001 (p <0.05). The results of the analysis concluded that there is a significant negative relationship between self-compassion and loneliness in early semester overseas students at Surabaya State University. It can be interpreted, the higher the self-compassion, the lower the loneliness felt by early semester overseas students at Surabaya State University. Conversely, the lower the self-compassion, the higher the loneliness felt by early semester overseas students at Surabaya State University.